2013
DOI: 10.5812/numonthly.5379
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative and Quantitative Study Monitoring Airborne Fungal Flora in the Kidney Transplant Unit

Abstract: BackgroundSolid organ transplantation patients are at high risk for opportunistic air-borne fungal infections due to using the potent immunosuppressive agents.ObjectivesThe current study aimed to qualitatively and quantitatively evaluate the fungal flora present in the air of Kidney transplant unit of Baqiyatallah hospital.Materials and MethodsIn this prospective study, air samples from patient room, baths site, ICU and isolated room, corridor site and outside the ward were obtained by settled plate technique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…Airborne fungal [ spores are very important agents in nosocomial infection and respiratory diseases and their effect on human health linked with their genera, species and concentrations in air. 9,11 Many studies have showed the relationship between HAI or nosocomial infection and the existence of microorganisms in hospital environments, including in the air of wards. 3,8 As an example, HAI rates have ranged from 1% in parts of Europe and North America to more than 40% in certain parts of Asia, Latin America and Sub-Saharan Africa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Airborne fungal [ spores are very important agents in nosocomial infection and respiratory diseases and their effect on human health linked with their genera, species and concentrations in air. 9,11 Many studies have showed the relationship between HAI or nosocomial infection and the existence of microorganisms in hospital environments, including in the air of wards. 3,8 As an example, HAI rates have ranged from 1% in parts of Europe and North America to more than 40% in certain parts of Asia, Latin America and Sub-Saharan Africa.…”
Section: Discussionmentioning
confidence: 99%
“…10 The Petri dishes were put at a height of 100-150 cm above the ground level during sampling for 20 min. 11 Finally over a three-month period, 108 plates were exposed to selective wards indoor air and 84 plates to outdoor air and samples were collected.…”
Section: Air Sampling Proceduresmentioning
confidence: 99%
“…In this study, environments of all wards were contaminated with types of fungi. Several researchers isolated a variety of fungi with different proportions from indoor environments of hospitals (7,15,18,(20)(21)(22)(23)(24)(25). In this study, among filamentous fungi, Cladosporium spp.…”
Section: Discussionmentioning
confidence: 99%
“…Although, fungal spores have the capacity to develop into different environments, they are considered inoffensive in immunocompetent subjects, but fatal in hospital inpatients receiving imunosuppressive medication (Afshari et al, 2013). It should be considered factors such as the fungal concentration, genus and species diversity, as well as their distribution characteristics in the environment, as shocking when considering the immunocompromised patients'condition (Zhang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%